Financial assistance measures in the euro area from 2008 to 2013: statistical framework and fiscal impact - Henri Maurer; Patrick Grussenmeyer (European Central Bank (ECB), 2015)
This paper summarises the accounting principles and methodology used by statisticians within the European System of Central Banks (ESCB) to assess the impact on the government's fiscal position of the assistance measures undertaken to support the financial sector during the financial crisis. It then presents for the euro area and its participating countries the main fiscal impact of these measures for the period 2008-2013. The results are mainly structured around three important questions for the wider public: (i) What is the magnitude of the financial resources needed by governments to provide financial support? (ii) What is the current gain or loss to governments from interventions to support the financial sector? And (iii) How did the guarantees provided by governments to the financing sector change over the period? Finally, the paper discusses further accounting challenges associated with this topic.
Keywords: H81; 330; bailout measures; capital transfers to the financial sector; change in net financial worth on balance sheet; earmarking and recording imputation; financial needs and estimated loss; impact on government debt and deficit